1991
DOI: 10.1038/hdy.1991.83
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the onychophoran Plicatoperipatus jamaicensis

Abstract: The Onychophora are a relic taxon which diverged early in the arthropod radiation and have shown little morphological differentiation for several hundred million years. Jamaica has the richest onychophoran fauna in the Caribbean and although only five species are known, they represent 7 per cent of the global fauna. The present study involved an analysis of allozyme and mtDNA diversity in Plicatoperipatus jamaicensis, an endemic species which is the commonest onychophoran on the island. The work showed that P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…The fact that genetic and geographic distances within group A are not correlated also suggest absence of gene flow. With the exclusion of the Piano Flat peripatus, groups A and B have withingroup genetic distances similar to one another, and similar to a study of Jamaican peripatus which found mtDNA distances between presumed sister species of 3.3% (Hebert et al 1991). In the Jamaican example, species status was evident from the lack of gene flow encountered between sympatric peripatus using allozymes.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The fact that genetic and geographic distances within group A are not correlated also suggest absence of gene flow. With the exclusion of the Piano Flat peripatus, groups A and B have withingroup genetic distances similar to one another, and similar to a study of Jamaican peripatus which found mtDNA distances between presumed sister species of 3.3% (Hebert et al 1991). In the Jamaican example, species status was evident from the lack of gene flow encountered between sympatric peripatus using allozymes.…”
Section: Discussionsupporting
confidence: 49%
“…In a sense this is a reversal of the situation that arises from morphology-based analyses which, naturally, tend to underestimate biogenetic diversity (Avise 1994). In the study of Onychophora for instance, a group noted for their morphological conservatism, genetic methods have revealed extensive cryptic diversity , stimulated revision of morphology based taxonomy (Reid 1996) and provided insights into the origin of diversity within, and biogeography of, species (Hebert et al 1991;Gleeson et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the possibility of onychophoran migration across large expanses of oceans has been discussed and discounted previously (Poinar, 1996); however, there is good evidence for dispersal over comparatively shorter distances in the Carribean (Hebert et al, 1991;Monge-Najera, 1995). Hence if our phylogenetic reconstructions are to be taken at face value, and given current theories on vicariance patterns, this last possibility requires further investigation.…”
Section: Discussionmentioning
confidence: 88%
“…The traditions of taxonomy, set as they are in morphology, have tended to underestimate actual biological diversity in many groups and the use of molecular techniques has led to the discovery of numerous discrete genetic groupings within recognized species boundaries (Hebert et al, 1990;Eldridge & Close, 1992;Briscoe & Tait 1995). An empirical framework for the identification of species therefore exists, within which corollaries of subtle morphology and perhaps more importantly ecology can be explored (Mayr, 1942).…”
Section: Introductionmentioning
confidence: 98%